Sensitivity of High-Pitch Dual-Source Computed Tomography for the Detection of Anomalous Pulmonary Venous Connection in Infants - Well, Lennart; Weinrich, Julius Matthias; Meyer, Mathias; Kehl, Torben; Salamon, Johannes; Rüffer, André; Adam, Gerhard; Herrmann, Jochen; Groth, Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To evaluate the sensitivity, specificity, and interobserver reliability of high-pitch dual-source computed tomography angiography (CTA) in the detection of anomalous pulmonary venous connection (APVC) in infants with congenital heart defects and to assess the associated radiation exposure.Materials and Methods 78 pulmonary veins in 17 consecutively enrolled patients with congenital heart defects (6 females; 11 males; median age: 6 days; range: 1–299 days) were retrospectively included in this study. All patients underwent high-pitch dual-source CTA of the chest at low tube voltages (70 kV). APVC was evaluated independently by two radiologists. Sensitivity, specificity, positive (PPV) and negative predictive values (NPV), and interobserver agreement were determined. For standard of reference, one additional observer reviewed CT scans, echocardiography reports, clinical reports as well as surgical reports. In cases of disagreement the additional observer made the final decision based on all available information.Results Detection of APVC with high-pitch dual-source CTA revealed a good sensitivity (91 %) and specificity (99 %), with PPV and NPV of 98 % and 97 %. Interobserver agreement was almost perfect (Kappa = 0.84). The median DLP was 3.8 mGy*cm (IQR 3.3–4.7 mGy*cm) and the median radiation dose was 0.33 mSv (IQR 0.26–0.39 mSv).Conclusion High-pitch dual-source CTA in infants with congenital heart defects allows for accurate and reliable assessment of APVC at a low radiation dose.Key Points: Citation Format
Keywords: cardiac; CT-angiography; pediatric; pulmonary veins; radiation dose